2022
DOI: 10.1002/htj.22614
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fluid flow and heat transfer of a periodic magnetohydrodynamics nano non‐Newtonian liquid with Arrhenius activation energy and nonlinear radiation

Abstract: The focus of this study is to better understand the boundary layer phenomena of nonlinear radiative nano non-Newtonian (Casson) fluid flow caused by a stretched periphery with a periodic magnetic field and Arrhenius activation energy. The time-based controlling equations are translated into a suitable dimensionless form using the explicit finite difference (EFD) approach.However, to make the solution convergent, detailed stability and convergence criteria have been devised. In addition, the oscillatory form of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…All of the discussion that has been presented in the Section 6.1 are in a good agreement with the several published works. 3,4,7,9,16…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…All of the discussion that has been presented in the Section 6.1 are in a good agreement with the several published works. 3,4,7,9,16…”
Section: F I G U R Ementioning
confidence: 99%
“…The introduction of a magnetic phenomenon dramatically changes the mass transportation and heat transfer capabilities of common electrically conducting flows, according to a number of anticipated experiments 1,2 . At recent time, Reza‐E‐Rabbi et al 3 studied out the influence of periodic MHD on a nanofluid flow. It has been illustrated that periodic magnetic factor influenced the heat transfer characteristics of nanofluid significantly under the impact of nonlinear radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Oyelakin et al [28] explored the time-dependent Casson fluid flow past a stretching sheet with activation energy and have proved that activation energy factor has upsurge the concentration characteristics of fluid. Reza-E-Rabbi et al [29] characterized the thermal flow transportation of MHD nanofluid with activation energy and nonlinear thermal radiation and found that the velocity has declined while thermal profile has expanded with augmenting values of solid volume fraction. Yasir et al [30] inspected the radiative nanoliquid flow over a cylinder subject to activation energy.…”
Section: Introductionmentioning
confidence: 99%
“…Reza‐E‐Rabbi et al. [29] characterized the thermal flow transportation of MHD nanofluid with activation energy and nonlinear thermal radiation and found that the velocity has declined while thermal profile has expanded with augmenting values of solid volume fraction. Yasir et al.…”
Section: Introductionmentioning
confidence: 99%
“…They also used the keller box method. Reza-E-Rabbi et al 34 studied out the investigation of heat transfer and fluid flow of a periodic MHD nano non-Newtonian fluid with Arrhenius activation energy and nonlinear radiation. They applied the explicit finite difference (EFD) approach for further analysis.…”
Section: Introductionmentioning
confidence: 99%